Control and monitoring of irrigation Water Pumping System by IoT - Hezlaoui Abdelhak; Zegheb Mohammed; Mebarki Abdallah (University of Shahid Hama Lakhdar - El Oued, 2024)
The Internet of Things (IoT) is a multidisciplinary concept that includes a wide range of application domains and device capabilities. The IoT technology provides a platform that allows apparatus to be monitored by sensors ,connected using a communication channel, and controlled remotely across a network infrastructure. This project represents the IoT-based remote monitoring, control, and protection of irrigation water pumping systems. The sensors measure parameters; namely supply voltage and motor current to estimate operating conditions and provide protection . The measured parameters are sent to the user through the SIM800L GSM module for remote monitoring and control purposes. Blnky android application has been developed to provide a better user interface, timer-based operation, status of pump and feedback notifications, etc. Protection to the pump (3-Փ Induction Motor) is provided through an ESP32 microcontroller. Appropriate relay characteristics are programmed in the microcontroller for protection against various types of faults like thermal overload, single phasing, under/over voltage voltage imbalance, reverse rotation. The system is tested in the lab and it is observed that all the protections are working satisfactorily.إنترنت الأشياء (IoT) هو مفهوم متعدد التخصصات يتضمن نطاقًا واسعًا مجالات التطبيق وقدرات الجهاز. توفر تقنية إنترنت الأشياء منصة تسمح بمراقبة الأجهزة بواسطة أجهزة استشعار، متصلة باستخدام قناة اتصال، ويتم التحكم فيها عن بعد عبر البنية التحتية للشبكة. هذا يمثل المشروع المراقبة والتحكم والحماية عن بعد المستندة إلى إنترنت الأشياء أنظمة ضخ مياه الري. أجهزة الاستشعار قياس المعلمات. وهي العرض الجهد والتيار المحرك لتقدير ظروف التشغيل وتوفير الحماية. يتم إرسال المعلمات المقاسة إلى المستخدم من خلال وحدة SIM800L GSM أغراض المراقبة والتحكم عن بعد. لقد تم تطبيق Blnky android تم تطويره لتوفير واجهة مستخدم أفضل وتشغيل يعتمد على المؤقت وحالة المضخة وإشعارات التعليقات وما إلى ذلك. توجد حماية للمضخة (المحرك التعريفي 3-). المقدمة من خلال متحكم ESP32. خصائص التتابع المناسبة هي مبرمج في المتحكم الدقيق للحماية من أنواع مختلفة من الأخطاء مثل الحمل الحراري الزائد، مرحلة واحدة، عدم توازن الجهد الكهربي أو الزائد، العكسي تناوب. تم اختبار النظام في المعمل ولوحظ أن كافة وسائل الحماية موجودة العمل بشكل مرضي.
Master's theses: specializing Electrical control
Keywords: Control; monitoring of irrigation Water; Pumping System; IoT; التحكم ومراقبة مياه الري ونظام الضخ وإنترنت الأشياء